ANCAMAN KRISIS EKONOMI GLOBAL DARI DAMPAK PENYEBARAN VIRUS CORONA (COVID-19) - SRI WAHYUNI HASAN; Stanny Sicilia Rawung; Ferry Lourens Sampel Korompis (Jurnal Equilibrium, 2022)
Abstract The Corona virus that is present in the midst of society in 2020 really grabs attention. The visible impacts not only affect public health, but also affect the country's economy. Even now the world economy is experiencing heavy pressure caused by the covid-19 virus. This topic will discuss the global impact of the presence of the corona virus or its scientific name is known as Covid-19. The research method used is descriptive qualitative by describing phenomena and existing literature. The results of this study indicate that looking at economic development and influence is not only limited to the scope of the economy itself. However, the economy can also be affected by culture and health. This is evidenced by the spread of the Corona virus which has a negative impact on the world economy. Keywords: Corona, Covid-19, Economy.